Implementasi Etika Profesi dalam Kehidupan Mahasiswa Sastra Inggris Universitas Bumigora - Soegiarto, Herryono; Fathoni, Muhammad; syamsurrijal, syamsurrijal (Jurnal Ilmu Sosial dan Humaniora, 2024)
The role of ethics in the lives of students is very important. It equips them with the ability to distinguish between what is right and what is wrong, thus enabling them to behave in a polite, courteous and responsible manner. Violations or deviant behaviour committed by prospective lecturers need to be observed, especially those related to professional ethics. Therefore, there is a need to conduct research on the application of professional ethics early in the lives of English Literature students who aspire to become lecturers. This research will use a literature review approach, involving a collection of books, academic articles and other relevant sources that explore the application of professional ethics in the lives of students. The data collected will be analysed descriptively. The findings of this study highlight the need for continuous effort in the application of professional ethics. Future teachers of English literature will develop the habit of implementing effective learning strategies by consistently practising the suggested efforts, which will prove beneficial when working with students in the future.